The Effect of DLC Surface coatings on microabrasive wear of Ti-22Nb-6Zr obtained by powder metallurgy - Gobbi, Silvio José (2024)
Titanium alloys have a high cost of production and exhibit low resistance to abrasive wear. The objective of this work was to carry out diamond-like carbon (DLC) coating, with dissimilar thicknesses, on Ti-22Nb-6Zr titanium alloys produced by powder metallurgy, and to evaluate its microabrasive wear resistance. The samples were compacted, cold pressed, and sintered, producing substrates for coating. The DLC coatings were carried out by PECVD (plasma-enhanced chemical vapor deposition). Free sphere microabrasive wear tests were performed using alumina (Al2O3 ) abrasive suspension. The DLC-coated samples were characterized by scanning electron microscopy (SEM), Vickers microhardness, coatings adhesion tests, confocal laser microscopy, atomic force microscopy (AFM), and Raman spectroscopy. The coatings did not show peeling-off or delamination in adhesion tests. The PECVD deposition was effective, producing sp2 and sp3 mixed carbon compounds characteristic of diamond-like carbon. The coatings provided good structural quality, homogeneity in surface roughness, excellent coating-to-substrate adhesion, and good tribological performance in microabrasive wear tests. The low wear coefficients obtained in this work demonstrate the excellent potential of DLC coatings to improve the tribological behavior of biocompatible titanium alloy parts (Ti-22Nb-6Zr) produced with a low modulus of elasticity (closer to the bone) and with near net shape, given by powder metallurgy processing.